Assessment of the Quality of Synchronization Reference Signals in IP-Networks Based on Synchronization Equipment Control Systems (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2020)
Control system TimePictra and SyncView Plus synchronization equipment considered, which allow measurements in packet networks. In the latest versions of these control systems, it became possible to measure the stability parameters of outgoing and incoming synchronization signals on network synchronization equipment by means that are hardware implemented in this equipment and supported by the corresponding software in TimePictra and SyncView Plus control systems. TimePictra and SyncView Plus control systems make it possible to perform such internal measurements in packet networks. For example, PDV (Packet Delay Variation), packet MTIE (Maximum Time Interval Error), packet TDEV (Time Deviation), packet minTDEV measurements. That is, the measurement ideology that Microsemi proposed in its TimeAnalyzer 7500 measuring device has seamlessly switched to the synchronization network itself. Based on the considered control systems, the possibility of creating a monitoring system - synchronization signals stability (but today with certain limitations). The principles of creating a modern system for monitoring the synchronization network based on signal analysis using the NTP(Network Time Protocol) and PTP (Precision Time Protocol) protocols are proposed. A monitoring scheme for the quality of reference synchronization signals using the PTP and NTP protocols presented, which includes two local sources. One based on the GPS receiver (Global Positioning System). Second based on the local PTP1 server. PTP1 connected to the calibration circuit and the outgoing signal connected to the averaging scheme. It is also conditionally possible to replace the PTP server with NTP. The scheme considered universal for two protocols. A prototype of the interaction between the three NTP nodes and the central server described. This prototype makes it possible to demonstrate the principles of monitoring by majority rules. In case of accumulation of a sufficient amount of data, you can create a graph or fill in data arrays for further analysis.